1989
DOI: 10.1073/pnas.86.19.7580
|View full text |Cite
|
Sign up to set email alerts
|

Protection of atrial natriuretic factor against degradation: diuretic and natriuretic responses after in vivo inhibition of enkephalinase (EC 3.4.24.11) by acetorphan.

Abstract: Atrial natriuretic factor (ANF) might be beneficial in several cardiovascular disorders, but its poor oral absorption and rapid inactivation in vivo have so far prevented its use in therapeutics. We have assessed the role of enkephalinase (membrane metallo-endopeptidase, EC 3.4.24.11) in the in vivo inactivation of ANF in mice and healthy human volunteers by evaluating the effects of acetorphan, a potent inhibitor.In mice, the degradation of 125I-labeled ANF was markedly delayed, as shown by the levels of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
55
0

Year Published

1991
1991
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(57 citation statements)
references
References 30 publications
2
55
0
Order By: Relevance
“…10,17 However, a reduction in blood pressure has not been clearly demonstrated in normotensive subjects, 10,18,20,21 and two studies have even reported an increase in blood pressure 22,23 despite the potent vasodilator actions of the natriuretic peptides. 12,13,16 Also, several studies on hypertensive patients 19,[32][33][34][35] have not demonstrated a reduction in blood pressure.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…10,17 However, a reduction in blood pressure has not been clearly demonstrated in normotensive subjects, 10,18,20,21 and two studies have even reported an increase in blood pressure 22,23 despite the potent vasodilator actions of the natriuretic peptides. 12,13,16 Also, several studies on hypertensive patients 19,[32][33][34][35] have not demonstrated a reduction in blood pressure.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, increasing the circulating concentrations of ANP through inhibition of NEP is an attractive therapeutic approach to a number of cardiovascular diseases such as hypertension and heart failure. 16 However, although NEP inhibitors increase circulating ANP concentrations in humans and cause the expected natriuresis, 10,17-19 they do not generally lower blood pressure in normotensive subjects. 10,18,20,21 Indeed, both candoxatril 22 and candoxatrilat 23 have been reported as raising blood pressure in normotensive subjects.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The physiological implication of NEP in the inactivation of these messenger peptides was confirmed in vivo by the design and use of selective and potent inhibitors, e.g. thiorphan (21)(22)(23)(24). These functions of NEP and the design of specific inhibitors thereof are of considerable interest, because the inhibitors of NEP have recently been introduced in human gastroenterologic (25) and cardiovascular (26) therapeutic fields.…”
mentioning
confidence: 99%